Troubling the Waters : Black-Jewish Relations in the American Century - Greenberg, Cheryl Lynn (Book collections on Project MUSE., 2006)
Was there ever really a black-Jewish alliance in twentieth-century America? And if there was, what happened to it? In Troubling the Waters, Cheryl Greenberg answers these questions more definitively than they have ever been answered before, drawing the richest portrait yet of what was less an alliance than a tumultuous political engagement--but one that energized the civil rights revolution, shaped the agenda of liberalism, and affected the course of American politics as a whole. Drawing on extensive new research in the archives of organizations such as the NAACP and the Anti-Defamation League.